NUTRIENT DEFICIENCES OF FIELD CROPS - PRAKASH KUMAR; MANOJ KUMAR SHARMA (Nosworthy way CABI, 2013)
This book, richly illustrated with over 700 coluor photographs, provide a visual field identification guide for symptomsof the most common nutrient deficiencies in field crops, covering all stages of occurance.
Nutrient Deficiencies in cereal crops Nutrient Deficiencies in pulse crops Nutrient Deficiencies in oilseed crops Nutrient Deficiencies in cash crops
Keywords: Guid to Diagnosis and Management